A Comparative Study on the Confinement Models of High-Strength Steel Fiber Concrete - Nur Fithriani F. Cholida; Antonius; Lintang Enggartiasto (Department of Civil and Environmental Engineering, Faculty of Engineering, Universitas Gadjah Mada, 2022)
Since the last four decades, the behavior of concrete contains of steel fiber, or often called steel fiber concrete, with a wide range of compressive strength has been carried out. Generally, the results of the experimental program produced a material which has a more ductile compared with normal concrete or concrete without fiber. Due to the ductility properties of the material, it is very suitable for use as an earthquake-resistant structural material. At the same time, the behavior of high-strength steel-fiber concrete has also investigated, one of which is about confined high-strength steel-fiber concrete. Analytical models of confined high-strength steel fiber concrete have been developed in various preliminary studies, with their characteristics derived based on the experimental results. Therefore, this research evaluated the models of confined high-strength steel-fiber concrete proposed by Mansur et al., Hsu and Hsu, and Paultre et al. The evaluation includes stress-strain behavior, strength enhancement of confined concrete (f'cc/f'co) or K value, the increase in confined concrete strain (ε'cc/ε'co), and strain of confined concrete when the stress has dropped by 50 percent against its unconfined strain (εcc50/εc50). The comparison method was carried out using a statistical approach and stress-strain simulation. Evaluation results showed significant predictive differences in confinement models in terms of post-peak behavior and parameters ε'cc/ε’co and εcc50/εc50. Prediction of confinement models on the value of f'cc/f’co to the experimental results has a coefficient of variation above 10%. The result further showed that a modified model of confined high-strength steel-fiber concrete was proposed and able to simulate the stress-strain behavior.